Y5 receptor signalling counteracts the anorectic effects of PYY3‐36 in diet‐induced obese mice. (22nd October 2017) - Shi, Y.‐C.; Ip, C. K.; Reed, F.; Sarruf, D. A.; Wulff, B. S.; Herzog, H.
Abstract: Peptide YY 3‐36 (PYY3‐36) is known as a critical satiety factor that reduces food intake both in rodents and humans. Although the anorexic effect of PYY3‐36 is assumed to be mediated mainly by the Y2 receptor, the involvement of other Y‐receptors in this process has never been conclusively resolved. Amongst them, the Y5 receptor (Y5R) is the most likely candidate to also be a target for PYY3‐36, which is considered to counteract the anorectic effects of Y2R activation. In the present study, we show that short‐term treatment of diet‐induced obese wild‐type (WT) and Y5R knockout mice (Y5KO) with PYY3‐36 leads to a significantly reduced food intake in both genotypes, which is more pronounced in Y5R KO mice. Interestingly, chronic PYY3‐36 infusion via minipumps to WT mice causes an increased cumulative food intake, which is associated with increased body weight gain. By contrast, lack of Y5R reversed this effect. Consistent with the observed increased body weight and fat mass in WT‐treated mice, glucose tolerance was also impaired by chronic PYY3‐36 treatment. Again, this was less affected in Y5KO mice, suggestive of a role of Y5R in the regulation of glucose homeostasis. Taken together, our data suggest that PYY3‐36 mediated signalling via Y5 receptors may counteract the anorectic effects that it mediates via the Y2 receptor (Y2R), consequently lowering bodyweight in the absence of Y5 signalling. These findings open the potential of combination therapy using PYY3‐36 and Y5R antagonists to enhance the food intake reducing effects of PYY3‐36.